The Study of Triple-Dip La Nina Phenomenon (2020-2023) and Its Impact on Atmospheric Dynamics and Rainfall in The Indonesian Region - Alhadid, Bai’at; Nugroho, Anwar Budi (Proceeding International Conference on Religion, Science and Education, 2024)
La Nina is one of the global-scale phenomena that occur in Pacific Ocean. In general, this phenomenon can increase rainfall in Indonesia. La Nina events can last for one year, two years, or even up to three years. When La Nina persists or lasts for three years, it is referred to Triple-Dip La Nina. One such Triple-Dip La Nina occurred during 2020 to 2023. Research on La Nina in Indonesian has been extensive. However, research specifically on Triple-Dip La Nina, particularly during 2020 to 2023, has not been conducted extensively. Therefore, this study aims to analyze Triple-Dip La Nina phenomenon that occurred during 2020 to 2023 and its impact on atmospheric dynamics and rainfall in Indonesia The results showed that the formation of the Triple-Dip La Nina was caused by the intrusion of cold anomalies from the southeastern subtropical region towards the equator of the East Pacific Ocean and the strengthening of the southeast trade wind which was associated with the east trade wind in the equatorial Pacific. Triple-Dip La Nina had varying impacts on atmospheric dynamics and rainfall in Indonesia. During each time period, only the northern and eastern parts of Indonesia, which are closest to the Pacific Ocean, consistently responded positively and were influenced by the Triple-Dip La Nina. In general Triple-Dip La Nina affects almost all regions of Indonesia during JJA (dry season) and SON (transition from dry season to rainy season) periods. During this period there was a strengthening of zonal winds (up to 5 - 7 m/s), an increase relative humidity (up to 6 - 20%) and rainfall (up to 150 mm) in almost all regions of Indonesia.